Diagnostic Approach to Patients with Hepatic Abscess: A Case Report - Made Ayu Agustia Pradnyani; I Made Dwija Suarjana (Al Makki Health Informatics Journal, 2025)
Hepatic abscess is a severe infection characterized by pus accumulation within the liver, often caused by bacterial or amoebic pathogens. This case report discusses the diagnostic challenges and management of bilateral hepatic abscesses in a resource-limited setting. A 43-year-old male presented with right upper quadrant abdominal pain, jaundice, and systemic symptoms. Diagnostic investigations, including ultrasonography and contrast-enhanced CT scan, revealed abscesses in the right and left hepatic lobes. Laboratory findings showed leukocytosis, hypoalbuminemia, and elevated liver enzymes. The patient was treated with empiric antibiotics and underwent laparotomy for abscess drainage, yielding 1700 cc of pus. Postoperative recovery was uneventful, with significant clinical improvement. This study highlights the importance of a combined medical and surgical approach in managing complex hepatic abscess cases, particularly in settings with limited diagnostic resources. The findings emphasize early diagnosis, multidisciplinary care, and tailored treatment strategies to improve outcomes for patients with hepatic abscesses, especially in underserved regions.